Understanding and Implementation of Religious Tolerance Verses Among High School Boarding School Students in Soloraya - Hasan, Moh Abdul Kholiq; Mujahid, Dhestina Religion; Hikmawati, Ari; Hardew, Ayatullah Kutub (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This qualitative research aims to determine the understanding and application of religious tolerance verses among boarding school high school students in the Soloraya area. Data were collected through questionnaires and interviews with students and teachers. The findings show a positive understanding of religious tolerance verses in such schools. Students gain this understanding through formal and informal social guidance and interaction. They display tolerant behavior towards both Muslim and non-Muslim individuals. A variety of factors contribute to the development of tolerant attitudes, including student background, teacher understanding, effective classroom management, family roles, and harmonious relationships between school and family. Boarding schools such as MATIQ Isy Karima, Muhammadiyah Trensains, IT Al-Huda, Daarul Fath, Baitul Qur'an, and Al-Muayyad have implemented the values of tolerance through formal and informal activities. The article recommends concrete measures to increase tolerance among boarding school students, such as the implementation of a multicultural pesantren curriculum, visits by religious leaders, inclusive social activities, house of worship visits, and interfaith seminars